2013
DOI: 10.1017/s0950268813000848
|View full text |Cite
|
Sign up to set email alerts
|

Serotype and surface protein gene distribution of colonizing group B streptococcus in women in Egypt

Abstract: Group B streptococcus (GBS) is a leading cause of neonatal sepsis and meningitis. We determined the distribution of serotypes and surface protein encoding genes of GBS strains from pregnant and non-pregnant women in Egypt. Vaginal swabs from 364 women were screened by culture and 100 (27.4%) yielded GBS. Serotype V was the most predominant (33%), followed by serotypes II (17%), III (15%), Ia (14%), VI (12%), Ib (8%) and IV (1%). The most common surface protein genes were epsilon (27%), alp3 (26%), bca (18%), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
5
24
1
Order By: Relevance
“…In the present study, the rate of GBS among pregnant women was 26.5%, which is in agreement with other Egyptian studies 13,29 and higher than the rates reported in others. 30,31 According to a review article published in 2010, which consists of 76 original articles, the results demonstrated that Middle East are accounted for high risk countries for GBS colonization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the rate of GBS among pregnant women was 26.5%, which is in agreement with other Egyptian studies 13,29 and higher than the rates reported in others. 30,31 According to a review article published in 2010, which consists of 76 original articles, the results demonstrated that Middle East are accounted for high risk countries for GBS colonization.…”
Section: Discussionsupporting
confidence: 93%
“…-The mean age of pregnant women carriers for GBS was (25.4 ± 2.9). GBS colonization was common mostly in the age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and this finding was statistically significant (p = 0.01). GBS colonization was statistically significantly higher at 37 weeks of gestation (p = 0.002), among women who had frequent antenatal visits (p=<0.001), and who adopted the condom contraceptive method (p=<0.001).…”
Section: Demographic Data Resultsmentioning
confidence: 90%
“…Epidemiological distribution of these 10 serotypes can vary depending on geographical region, population under study and the source of the bacterial isolate 48. Studies from Gambia49 and Egypt50 have reported serotype V as the most common serotype, while in South Africa and Morocco13 51 52 serotypes Ia and III are dominant with a range of 30%–40% and serotype V only with 10% of isolates.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that S. agalactiae strains usually carry at least one of the alpha-like proteins, of which proteins Epsilon (Alp1), Alp2, Alp3, Alp4, Alpha-C and Rib have been extensively studied [17], although several bovine and human strains have been reported to be negative for any of the six proteins [16,17,18]. In this study, the multiple PCR assay for detecting Alp genes showed that 92% of the tested bovine isolates were non-typeable, possibly due to mismatch of the primers for genes encoding alpha-like proteins in these isolates.…”
Section: Discussionmentioning
confidence: 99%